Secure Hybrid Beamformers Design in mmWave MIMO Wiretap Systems - Tian, Xiaowen; Liu, Qian; Wang, Zihuan; Li, Ming (IEEE systems journal, 2020)
Millimeter wave (mmWave) communications have been considered as a key technology to enable very high data rate in the fifth-generation applications. Multiple-input-multiple-output (MIMO) systems with hardware efficient analog/digital hybrid beamformer architecture have been widely considered to overcome the severe propagation loss of the mmWave channels. However, physical layer security in the mmWave wiretap MIMO systems and secure hybrid beamformer design have not been well investigated. In this paper, we consider the problem of the hybrid beamformer design for the secure transmission in mmWave wiretap MIMO systems in order to protect the legitimate transmission from eavesdropping. We aim to develop efficient secure hybrid beamformer design algorithms for both codebook-free and codebook-based analog beamformer schemes with either high-resolution or low-resolution phase shifters. Particularly, when eavesdropper's channel state information (CSI) is known, we first propose a joint analog precoder and combiner design algorithm that can prevent the information leakage to the eavesdropper. Then, the digital precoder and combiner are computed based on the obtained effective baseband channel to further maximize the secrecy rate. If prior knowledge of the eavesdropper's CSI is unavailable, we develop an artificial-noise-based hybrid beamforming approach, which can disrupt eavesdropper's reception while maintaining the quality-of-service of the intended receiver at a prespecified level. Extensive simulation results validate the effectiveness of the proposed secure hybrid beamformer designs under different availabilities of eavesdroppers CSI.